Metode Pembinaan Pendidikan Akhlak Tingkat Sekolah Dasar - Sumiah Nasution (Journal on Education, 2023)
Morals are behaviors that arise from good or bad habits. They help us to know what is right and wrong, and what is useful or not useful for ourselves. This research is a mix of library research (using books and other sources) and field research (gathering data through observation and interviews). The field research part of this study involved talking to Islamic religious teachers in elementary schools. The results showed that the use of many methods and varied approaches in fostering moral education at the elementary school level has been implemented properly. The various methods used to try to change someone's behavior include advice, warning, punishment, and habituation. The curriculum includes lessons on morality, respect for parents and elders, and being honest in speech. Additionally, students are taught how to protect the environment and conserve natural resources. The obstacles faced by Ustad Dalam in promoting moral education among children are that he does not know whether the children's friends are of good or bad character. It is hoped that this research will be useful not only for school principals and teachers as reference materials, but also for all readers in general.